Spatial and temporal integration of rice, fish, and prawn in the coastal wetlands of central Kerala, India - Sasidharan, N.K.; Abraham, C.T.; Rajendran, C.G. (Journal of Tropical Agriculture, 2012)
The traditional system of growing tall rice (Oryza sativa L.) varieties during the monsoon season and prawn culture (prawn filtration) during summer season, locally known as pokkali, is a sustainable system of production harmoniously blended with natural processes like sea water inundation in the low-lying coastal zones of Kerala. A two year field study at Vyttila, Kerala, India evaluated spatial and temporal integration of high yielding pokkali rice genotypes with varying morphological characters (VTL3, culture-1026, and ‘Chettivirippu’ mutant) with fish [etroplus (Etroplus suratensis Bloch), rohu (Labeo rohita F. Hamilton) and tilapia (Oreochromis mosambicus Peters)] and tiger prawn (Peneaus monodon Fabricus) grown in succession. Culture-1026 showed better growth and yield (4391 kg ha–1) over VTL3 (2434 kg ha–1) and ‘Chettivirippu’ mutant (3950 kg ha–1). Among the fishes tried, all male population of tilapia outperformed etroplus and rohu in terms of survival (37.6, 0.0, and 16% respectively) and yield (216.7, 0.0, and 12.7 kg ha–1 respectively) when grown simultaneously with rice. Inclusion of tiger prawn as a rotational component during summer enhanced profitability (prawn yield 425 kg ha–1) and benefit-cost ratio (2.03). Although no direct effect of the components on pH, electrical conductivity, organic carbon content, available phosphorus, available potassium, and available sodium of the soil were noted, seasonal variations in water quality and consequent changes in soil properties were evident. Compatibility of the components, stable yields, favourable soil physico-chemical and hydrological parameters, and economic returns contribute to the sustainability of this production system.